2020
DOI: 10.1017/ice.2020.1241
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use during end-of-life care: A systematic literature review and meta-analysis

Abstract: Background: We performed a systematic literature review and meta-analysis measuring the burden of antibiotic use during end-of-life (EOL) care. Methods: We searched PubMed, CINAHL (EBSCO platform), and Embase (Elsevier platform), through July 2019 for studies with the following inclusion criteria in the initial analysis: antibiotic use in the EOL care patients (advanced dementia, cancer, organ failure, frailty or multi-morbidity). If the number of patients in palliative care consultation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…The frequency in which antimicrobials were used at the EOL-59% in the last week of life and 5% on the day of death-was consistent with other studies. 2,4,7,24 Our findings provide a unique clinical picture of patients with cancer who more commonly receive antimicrobials at EOL: those more likely to be older, with clinical signs of infection, who receive diagnostic and radiologic testing, and those with higher rates of palliative care or infectious disease consultations. Other variables significantly associated with EOL antimicrobial use included the presence of an indwelling foreign device, mechanical ventilation, completed advance directives, orders for EOL care, and death in the ICU.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The frequency in which antimicrobials were used at the EOL-59% in the last week of life and 5% on the day of death-was consistent with other studies. 2,4,7,24 Our findings provide a unique clinical picture of patients with cancer who more commonly receive antimicrobials at EOL: those more likely to be older, with clinical signs of infection, who receive diagnostic and radiologic testing, and those with higher rates of palliative care or infectious disease consultations. Other variables significantly associated with EOL antimicrobial use included the presence of an indwelling foreign device, mechanical ventilation, completed advance directives, orders for EOL care, and death in the ICU.…”
Section: Discussionmentioning
confidence: 87%
“…The majority of patients with cancer receive antimicrobials during terminal admissions, in palliative care units, and at the time surrounding death-even in the absence of infection. [1][2][3][4][5][6][7][8] In fact, one systematic review reported that more than 50% of patients with advanced cancer at the end of life (EOL) received antimicrobials (n = 15 studies). 2 Prophylactic and empiric antimicrobial use is common in cancer patients due to immunocompromised states and resultant non-specific signs of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetaminophen was speculated to be used for pain management and for fever with infectious diseases. Antibiotics are commonly prescribed in the end-of-life stage for infectious diseases 31. Expectorants and tulobuterol (a β agonist) patch formulation were possibly prescribed due to the increased bronchial secretion towards the end-of-life stage, although the efficacy of these drugs to relieve respiratory secretion symptoms has not been shown 32.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced cancer are prone to infections due to cancer-treatment-induced immunosuppression, barrier dysfunctions, and the use of immunomodulating drugs like corticosteroids [ 9 ]. Antibiotic treatment in palliative care patients may not necessarily aim for, or result in, life prolongation, albeit some studies demonstrated an improved survival after the successful treatment of infections [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%